2007
DOI: 10.1016/j.rmed.2006.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A proof of concept study to evaluate stepping down the dose of fluticasone in combination with salmeterol and tiotropium in severe persistent asthma

Abstract: We conducted a double blind, randomised, placebo-controlled, crossover study evaluating the effects of halving inhaled steroid dosage plus salmeterol, or salmeterol and tiotropium. Eighteen life-long non-smoking severe asthmatics [mean FEV(1) 1.49 l (51%)] were run-in for 4 weeks on HFA-fluticasone propionate 1000 microg daily, and were subsequently randomised to 4 weeks of either (a) HFA-fluticasone propionate 500 microg BD/salmeterol 100 microg BD/HFA-tiotropium bromide18 microg od; or (b) fluticasone propio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 36 publications
1
62
0
8
Order By: Relevance
“…Tiotropium bromide, a recently developed anticholinergic, is a long-acting bronchodilator with a well-established effectiveness for treating chronic obstructive pulmonary disease [2]. Although some subgroups of asthmatics seem to respond better to anticholinergics, the pathophysiological features of these responders have yet to be established [3,4]. Previous studies that aimed to identify asthma subgroups which respond better to anticholinergics have suggested the following clinical features: patients with nocturnal symptoms, chronic asthma showing concurrent fixed airway obstruction, intrinsic asthma with longer duration of disease and nonatopic asthma [1,5].…”
Section: To the Editormentioning
confidence: 99%
“…Tiotropium bromide, a recently developed anticholinergic, is a long-acting bronchodilator with a well-established effectiveness for treating chronic obstructive pulmonary disease [2]. Although some subgroups of asthmatics seem to respond better to anticholinergics, the pathophysiological features of these responders have yet to be established [3,4]. Previous studies that aimed to identify asthma subgroups which respond better to anticholinergics have suggested the following clinical features: patients with nocturnal symptoms, chronic asthma showing concurrent fixed airway obstruction, intrinsic asthma with longer duration of disease and nonatopic asthma [1,5].…”
Section: To the Editormentioning
confidence: 99%
“…Recent research has indicated that the addition of salmeterol and tiotropium in association with halving the dose of fl uticasone propionate in severe asthmatics leads to small improvements in effort-dependent and -independent pulmonary function outcomes, but not in quality-of-life scores [46]. The magnitude of improvements in pulmonary function provided by salmeterol and tiotropium were not predicted by the acute reversibility to salbutamol and ipratropium.…”
Section: Which Type Of Inhaled Bronchodilator Is Most Effi Cacious Inmentioning
confidence: 99%
“…Moreover, adding tiotropium bromide once daily as maintenance treatment in addition to at least high-dose ICSs combined with LABAs offers significant potential to improve airway patency in patients with severe persistent asthma who are still symptomatic and obstructed on maximal therapy (Kerstjens et al, 2011). Furthermore, the addition of salmeterol/tiotropium bromide facilitates the step down of ICS in severe patients (Fardon et al, 2007).…”
Section: The Role Of Bronchodilators In the Management Of Asthmmentioning
confidence: 99%